Wacana Islam Populer dan Kelahiran Ustaza Medsos di Ruang Publik Era Digital - Sukma Ari Ragil Putri; - - (Universitas Tidar, 2018)
Social media has become a public sphere that used by today's society. The development of social media, supported by the increasing of smartphone user made people who had been reluctant to read to be ‘a good student’ in reading everything that are uploaded in social media, including Islam’s thought, theory, or doctrine. Over the past decade, Islam has been through some popularity stage, started from ‘nationalist’ Islam until what’s popular today as Islam 'according to shari'at'. Social media took a big role in the development of popular Islam. One of them is through the emergence of preachers who do da’wah activities in social media with all its advantages and limitations, such as Felix Siauw. This paper was trying to understand what discourse that led Islam ‘according to shari’at’ became popular today by observing and analyzing Felix Siauw’s Instagram account. As a result, this paper found out that this new ‘ustaz medsos’ is part of the cause that creates popular Islam as we know it.